Psalm 88: the gloomiest Psalm? - Prinsloo, W. S. (Old Testament Essays, 1992)
By way of a Forschungsgeschichte of Psalm 88 in particular, and the individual complaint in general, it is demonstrated that, despite years of research, there is no consensus or clarity on even the most basic questions and terminology in this area. This indicates the relativity of exegesis and calls for evaluation in terms of each exegete's own presuppositions. By means of this article I have attempted to make my own exegetical position clear.
free